Meningkatkan Hasil Belajar Pendidikan Pancasila Menggunakan Model Pembelajaran Cooperative Learning Tipe Teams Games Tournament bagi Siswa Kelas V SDN Bandar Lor 3 - Alaik Zulfikar Aziz (Universitas Nusantara PGRI Kediri, 2025)
This classroom action research was motivated by the inaccuracy of the model teacher in selecting the learning model, which resulted in boredom and lack of focus for students in following the learning process. This study aims to determine the